1940
DOI: 10.1002/hlca.194002301138
|View full text |Cite
|
Sign up to set email alerts
|

d, l‐α‐Tocopherol‐phosphorsäure‐ester

Abstract: Auch Versuche, 3,4-Dehydroa-tocopherol durch Erhitzen von 1,5 Teilen Trimethyl-hydrochinon, 2,9 Teilen 3,7,11,15-Tetramethylhexadecin-(1)-01-(3) (Formel I) und 0,5 Teilen Zinkchlorid im Bombenrohr auf 175O herzustellen, befriedigten in der Ausbeute nicht, wenn auch das Allophanat des 3,4-Dehydro-or-tocopherols dabei in geringer Menge erhalten wurde.Von den zahlreichen, fruher hergestellten Estern des d, I-a-Tocopherolsl) hatten die meisten sehr gute Vitamin-E-Wirkung gezeigt. Aus verschiedenen Grunden schien u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1941
1941
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Massive necrosis of the liver, produced in rats by diets low in cystine and high in cod liver oil, or containing alkali-treated casein as the sole source of protein, can be prevented by tocopherol administration (37). The mechanism of this protective action is not known, but it does not appear to be related to the usual vitamin E activity of tocopherol, since the protective dose is many times that required to prevent muscular dystrophy and testicular atrophy (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Massive necrosis of the liver, produced in rats by diets low in cystine and high in cod liver oil, or containing alkali-treated casein as the sole source of protein, can be prevented by tocopherol administration (37). The mechanism of this protective action is not known, but it does not appear to be related to the usual vitamin E activity of tocopherol, since the protective dose is many times that required to prevent muscular dystrophy and testicular atrophy (4).…”
mentioning
confidence: 99%
“…These findings suggest a defect in the absorption of intramuscularly administered dl-alpha-tocopherol similar to that observed in the rabbit (35) and in the rat (36 To eliminate the effects of faulty absorption from muscle, a readily absorbed, water-soluble, preparation of tocopherol suitable for parenteral injection was sought. Recent reports (35,37,38) suggested that the di-sodium salt of d-alpha-tocopheryl phosphate might meet these requirements. Preliminary experiments were carried out in rats with an intramuscular injection of 50 mg. in 0.5 cc.…”
mentioning
confidence: 99%